EVALUASI DAMPAK INFRASTRUKTUR PLBN TERHADAP PEREKONOMIAN DAN KONEKTIVITAS WILAYAH PERBATASAN - Amung Hidayat; Siswo Awaliyanto (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to evaluate the impact of constructing Cross-Border Posts (PLBN) on the local economy and connectivity of border areas. Using a descriptive qualitative approach, data were obtained through in-depth interviews, direct observations, and document review at PLBNs that have operated as centers of cross-border activities. The study's results demonstrate that the development of PLBN significantly contributes to enhancing economic activities, including the growth of MSMEs, increased cross-border trade volumes, and expanded job opportunities for local communities. On the other hand, the integration of PLBN with road networks and transportation infrastructure has been proven to improve accessibility, reduce logistics costs, and accelerate the mobility of goods and people in border areas. However, the study also identified several challenges, including inequality in supporting infrastructure, limited capacity among local business actors, and institutional barriers that reduce the effectiveness of PLBN as a driving force for the border economy. Overall, PLBN has excellent potential to catalyze economic development and regional connectivity; however, its long-term success requires the integration of cross-sectoral policies, improvement of basic services, and strengthening of regional governance.